Coupled Oceanic and Atmospheric Controls of Deglacial Southeastern South America Precipitation and Western South Atlantic Productivity - Meier, Karl J. F.; Jaeschke, Andrea; Rethemeyer, Janet; Chiessi, Cristiano M.; Albuquerque, Ana Luiza S.; Wall, Vincent; Friedrich, Oliver; Bahr, André (Frontiers in Marine Science, 2022)
Various mechanisms were proposed as substantial drivers of (sub)tropical South American hydroclimate changes during the last deglaciation. However, the interpretation of past precipitation records from the regions affected by the South American Summer Monsoon, the dominant hydroclimatic system in (sub)tropical South America, still insufficiently consider feedbacks between oceanic and atmospheric processes evident in modern observational data. Here, we evaluate ocean-atmosphere feedbacks active in the region from 19 to 4 ka based on a multi-proxy record comprising lipid biomarker, bulk sediment elemental composition and foraminiferal geochemistry from a sediment core retrieved from the tropical western South Atlantic offshore eastern Brazil at 22°S. Our proxy data together with existing paleoclimate records show that the consideration of large scale synoptic climatic features across South America is crucial for understanding the past spatio-temporal rainfall variability, especially during the last deglaciation. While the paleohydrological data from our study site show relatively stable precipitation across the deglaciation in the core region of the South Atlantic Convergence Zone, distinct hydroclimatic gradients developed across the continent during Heinrich Stadial 1, which climaxed at 16 ka. By then, the prevalent atmospheric and oceanic configuration caused more frequent extreme climatic events associated with positive rainfall in the northern portion of eastern South America and in the southeastern portion of the continent. These climatic extremes resulted from substantial warming of the sub(tropical) western South Atlantic sea surface that fostered oceanic moisture transport towards the continent and the reconfiguration of quasi-stationary atmospheric patterns. We further find that enhanced continental precipitation in combination with low glacial sea level strongly impacted marine ecosystems via enhanced terrigenous organic matter input in line with augmented nutrient release to the ocean. Extreme rainfall events similar to those that occurred during Heinrich Stadial 1 are likely to recur in South America as a consequence of global warming, because the projected reduction of the intra-hemispheric temperature gradient may lead to the development of atmospheric patterns similar to those in force during Heinrich Stadial 1.